Effect of Surfactant on Solution Properties of Amphoteric Hydrophobically Associating Polymer - Zhang, Jian; Ma, Panpan; Han, Lijuan (Asian Journal of Chemistry, 2014)
The interactions of sodium dodecylbenzenesulfonate with amphoteric hydrophobically associating polymer in aqueous solution were studied by laser light scattering and rheometer. The viscosity of the polymer has exhibited an increase at first and then decrease with the increase of surfactant concentration when salt concentration is low. Sodium dodecylbenzenesulfonate has a great influence on the elastic modulus of the polymer solution, while has a little influence on the viscous modulus. Moreover, the surfactant also has a great effect on the root mean square radius of gyration (<Rg>), hydrodynamic radius (<Rh>), the ratio of <Rg> to <Rh> and the apparent weight average molecular weight (Mw) of polymer.